Rescue or murder? The effect of prey adaptation to the predator subjected to fisheries - Yangke Shang; Minoru Kasada; Michio Kondoh (Ecology and Evolution)
Abstract The concept of “indirect evolutionary rescue” refers to the evolutionary adaptation of an interacting species that can save a focal species from extinction in an unfavorable environment. Although theories suggest that indirect evolutionary rescue may have essential impacts on catchments in the context of fisheries where artificial selection pressure from fishing can drive evolution, its generality and conditions remain uncertain. In this study, by investigating how prey adaptation affects the persistence of a predator subjected to selective harvest with an eco‐evolutionary predator–prey model, we find that prey adaptation tends to deteriorate (facilitate) predator persistence when predator's evolvability is high (low). In the system where the predator possesses high evolvability, selection by fisheries inhibits a predator's adaptation to prey, allowing the prey to escape predation by adaptation. Prey adaptation will affect predator persistence negatively, leading to evolutionary murder. Conversely, in the system where the predator's evolvability is low, the removal of predator individuals by fisheries relaxes predation pressure on prey, making the prey less defensive. Vulnerable prey affects predator persistence positively, resulting in indirect evolutionary rescue. The context‐dependent response of natural resources to fisheries identified in this study suggests that the eco‐evolutionary interplay should be considered for better natural resource management.